Perancangan Sistem Informasi Pengusulan Kenaikan Pangkat Berbasis Web Pada Korps Marinir TNI AL - Junaidi; Arif Rahman, Rians Aulia; Alvian Adhitya (Technomedia Journal, 2021)
ABSTRACT The rapid development of computer technology for the world of knowledge affects patterns and methods of work in all fields The Navy Marine Corps is one of the ASN offices tasked with protecting the Indonesian state in all fields. In order for research to be carried out properly and appropriately, of course there must be clear objectives, which has been established an implementation of the research. The data collection method is by conducting observations, interviews, and literature studies, the data obtained are analyzed in the form of Unified Modeling Language (UML) using Visual Paradigm 16.2 Software. The results of researchers' observations on the ongoing system process using Microsoft Word (manual). The promotion report is described using the Unified Modeling Language (UML). Based on the results of the research analysis of problems that occur in the Indonesian Navy Marine Corps that have been described in previous chapters, based on the results of the researchers' observations during the observations, it can be concluded that the application of proposing promotion of rank can simplify and speed up the process to make it faster, more precise and efficient. Keywords: Information, Promotion, and Marine Corps.